Dyspnea Measurement in Acute Heart Failure: A Systematic Review and Evidence Map of Randomized Controlled Trials - Zhang, Xiaoyu; Zhao, Chen; Zhang, Houjun; Liu, Wenjing; Zhang, Jingjing; Chen, Zhao; You, Liangzhen; Wu, Yuzhuo; Zhou, Kehua; Zhang, Lijing; Liu, Yan; Chen, Jianxin; et al. (Frontiers in Medicine, 2021)
Background: Dyspnea is the most common presenting symptom among patients hospitalized for acute heart failure (AHF). Dyspnea relief constitutes a clinically relevant therapeutic target and endpoint for clinical trials and regulatory approval. However, there have been no widely accepted dyspnea measurement standards in AHF. By systematic review and mapping the current evidence of the applied scales, timing, and results of measurement, we hope to provide some new insights and recommendations for dyspnea measurement. Methods：PubMed, Embase, Cochrane Library, and Web of Science were searched from inception until August 27, 2020. Randomized controlled trials with dyspnea severity measured as the endpoint in patients with AHF were included. Results: Out of a total of 63 studies, 28 had dyspnea as the primary endpoint. The Likert scale (34, 54%) and visual analogue scale (22, 35%) were most widely used for dyspnea assessment. Among the 43 studies with detailed results, dyspnea was assessed most frequently on days 1, 2, 3, and at 6 h after randomization or drug administration. Compared with control groups, better dyspnea relief were observed in experimental groups in 21 studies. Only four studies that assessed tolvaptan compared with control on the proportion of dyspnea improvement met the criteria for meta-analysis, which did not indicate any beneficial effect of dyspnea improvement on day 1 (RR: 1.16; 95% CI: 0.99-1.37; p=0.07; I2=61%). Conclusion: The applied scales, analytical approaches, and timing of measurement are in diversity, which has impeded the comprehensive evaluation of clinical efficacy of potential therapies managing dyspnea in AHF patients. Developing a more general measurement tool established on the unified uni-dimensional scales and standardized operation protocol to record the continuation and clinically significant difference of dyspnea variation may be a promising approach. In addition, to evaluate the effect of experimental therapies on dyspnea more precisely, the screening time and blinded assessment are factors that need to be considered.